2011
DOI: 10.1016/s0027-9684(15)30297-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient Complexity and Diabetes Quality of Care in Rural Settings

Abstract: Purpose Even though pay-for-performance programs are being rapidly implemented, little is known about how patient complexity affects practice-level performance assessment in rural settings. We sought to determine the association between patient complexity and practice-level performance in the rural United States. Basic procedures Using baseline data from a trial aimed at improving diabetes care, we determined factors associated with a practice’s proportion of patients having controlled diabetes (hemoglobin A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Third, patient complexity may explain a portion of the variability of diabetes control. We have previously found that glucose control (A1c ≤ 7%) was lower in the worst quartile of practices as compared to the best quartile of practices (19%‐23% vs. 75%‐76%) 31,32 . Practices in the worst quartile of control had higher proportions of younger patients, African Americans, and patients on insulin.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Third, patient complexity may explain a portion of the variability of diabetes control. We have previously found that glucose control (A1c ≤ 7%) was lower in the worst quartile of practices as compared to the best quartile of practices (19%‐23% vs. 75%‐76%) 31,32 . Practices in the worst quartile of control had higher proportions of younger patients, African Americans, and patients on insulin.…”
Section: Discussionmentioning
confidence: 91%
“…Practices in the worst quartile of control had higher proportions of younger patients, African Americans, and patients on insulin. Furthermore, practices in the worst quartile of control had a higher proportion of patients experiencing difficulty with self‐testing and keeping appointments 31 . Other studies have found that African Americans have higher A1c as compared to their white counterparts 33 and less self‐monitoring 34 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Some argue that this already occurs; in theory, yes, but in practice not necessarily in a uniform and consistent manner. 82,89,91,92 An existing challenge surrounding the commissioning services to support complexity is the dual challenge of patient complexity and system complexity. These are often perceived as antagonistic; we argue that that the paradigm shift is to view these in a synergistic way.…”
Section: Operationalising Complexitymentioning
confidence: 99%